VITAMIN D LEVEL AND CONDITION OF MINERAL BONE DENSITY IN CHILDREN WITH OBESITY AND OVERWEIGHT - Ashurova Maksuda Zhamshedovna; Garifulina Lilya Maratovna (Journal Park Publishing, 2022)
Examined 30 children with overweight and obesity, the facts of infringement of the mineral first bone density more expression conjugated with obesity, while marked by low supply of vitamin D in children and adolescents of school age, regardless of body weight
Keywords: obesity; children; bone mineral density